2016
DOI: 10.3389/fimmu.2016.00542
|View full text |Cite
|
Sign up to set email alerts
|

Complement Regulator FHR-3 Is Elevated either Locally or Systemically in a Selection of Autoimmune Diseases

Abstract: The human complement factor H-related protein-3 (FHR-3) is a soluble regulator of the complement system. Homozygous cfhr3/1 deletion is a genetic risk factor for the autoimmune form of atypical hemolytic-uremic syndrome (aHUS), while also found to be protective in age-related macular degeneration (AMD). The precise function of FHR-3 remains to be fully characterized. We generated four mouse monoclonal antibodies (mAbs) for FHR-3 (RETC) without cross-reactivity to the complement factor H (FH)-family. These anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 74 publications
7
47
1
Order By: Relevance
“…These results suggest that increased FHR-3 levels predispose to aHUS. This observation is in line with a previous study ( 21 ) that determined FHR-3 levels in 21 patients with aHUS (1.60 ± 0.57 µg/mL) and 21 controls (1.06 ± 0.53 µg/mL), although the difference in FHR-3 levels between their patient and control cohorts was smaller than in our study, which could well be related to the cohort size and the variation in allele frequency. In our study, 4% of the controls and 9% of the patients with aHUS carried the CFHR3*Del/Del genotype (i.e., homozygous CFHR3-CFHR1 deletion), frequencies comparable to the 2.9% and 12.4% observed in a French study comparing 70 controls and 117 patients with aHUS ( 22 ).…”
Section: Discussionsupporting
confidence: 93%
“…These results suggest that increased FHR-3 levels predispose to aHUS. This observation is in line with a previous study ( 21 ) that determined FHR-3 levels in 21 patients with aHUS (1.60 ± 0.57 µg/mL) and 21 controls (1.06 ± 0.53 µg/mL), although the difference in FHR-3 levels between their patient and control cohorts was smaller than in our study, which could well be related to the cohort size and the variation in allele frequency. In our study, 4% of the controls and 9% of the patients with aHUS carried the CFHR3*Del/Del genotype (i.e., homozygous CFHR3-CFHR1 deletion), frequencies comparable to the 2.9% and 12.4% observed in a French study comparing 70 controls and 117 patients with aHUS ( 22 ).…”
Section: Discussionsupporting
confidence: 93%
“…Hence, it is more likely that there is a difference in the Sf9-derived rhFHR-4A previously used ( 14 ) and the HEK293F-derived rhFHR-4A used here for the calibration of the assays. Considering the recently reported normal values for all other FHR proteins ( 6 , 18 , 21 , 22 ), ranging from 0.7 to 12 µg/mL (with FHR-1 being the most abundant FHR protein), it seems the values that we report for FHR-4A are likely to be correct.…”
Section: Discussionsupporting
confidence: 65%
“…Several reports have shown that recombinant FHR-4A and -4B indeed bind to known FH ligands and allow complement activation to occur in vitro ( 11 , 14 , 15 ). To date, normal levels of FHR-1, FHR-2, FHR-3, and FHR-5 have been reported and were found to be circulating at much lower concentration as compared to FH ( 6 , 18 , 21 , 22 ). In this report, we describe the circulating levels of FHR-4A in healthy individuals, using novel, well-characterized anti-FHR-4A mAbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, little information on the extrahepatic expression of the FHR proteins is available. Both CFHR3 mRNA and FHR-3 protein have been identified in retinal macrophages, while no FHR-3 expression was found in other retinal cell types ( 47 ). Extrahepatic synthesis of FH/FHRs most likely contributes to an efficient control of complement activation locally, but a relevant contribution to the plasma levels of these proteins is unlikely, considering the relative low expression compared to the hepatic source.…”
Section: Quantitation Of Fhr Proteinsmentioning
confidence: 99%